FORMATION OF THE ETHICS OF PROFESSIONAL ACCOUNTANTS FROM A MORAL STANDPOINT: ANALYSIS OF DECISIVE FACTORS AND THEIR INFLUNCE - Stonciuviene, Neringa; Naujokaitiene, Justina (European Scientific Journal, ESJ, 2014)
Economic decision-making by enterprise owners, potential investors and the managers and technologists of an organisation rely on information supplied by accountants. Insufficient or inappropriate understanding of the norms of ethics by accountants or individuals acting in their environment leads to the formation of accountants’ unethical behaviour and the problems of accounts handling and finance management. This study analysed the models of professional ethical behaviour presented in scientific literature and used for empirical studies as well as the possibility of their application during an assessment of accountants’ professional ethics in the context of their virtues and environment, selected the virtues of accountants and environmental factors having an influence on accountants’ motivation to behave ethically/unethically and evaluated the importance of these factors for the ethical behaviour of professional accountants. An analytical study design was used in order to develop a theory-based framework. Using Rest’s model of executives’ ethical behaviour, we analysed the impact of personal moral identification, business environment and the Code of Ethics for Professional Accountants on accountants’ professional ethics. In order to establish whether or not these factors predetermine ethical behaviour of professional accountants, an anonymous survey of professional accountants in business was conducted by asking them to evaluate whether or not the presented virtues and business environment-related cases that are likely to cause professional ethics problems are important in accountant’s work. Study results lead to the conclusion that the ethical behaviour perceived by accountants is predetermined by their virtues (a sense of duty, integrity, fairness, attentiveness, independence and selfconfidence). Meanwhile, neither a working environment of accountants nor knowledge of the Code of Ethics for Professional Accountants predetermines ethical behaviour.